Case formulation in clinical practice: Associations with psychological mindedness, attachment and burnout in staff working with people experiencing psychosis. (18th August 2015) - Hartley, Samantha; Jovanoska, Jelena; Roberts, Susan; Burden, Nicolas; Berry, Katherine
Abstract : Objectives: Case formulation can impact on therapeutic relationships, staff understanding and outcomes, which might be particularly important when working with complex mental health problems such as psychosis. However, the evidence base is equivocal and there is insufficient understanding around the staff‐related factors that influence effective psychological case formulation. This study investigated the influence of staff characteristics (both professional and personal) on case formulation skill. Design: This was a cross‐sectional study, with all of the measures collected at the same time point. Methods: Fifty staff members working on inpatient wards with individuals experiencing psychosis were recruited. Measures included independently rated case formulation skill and psychological mindedness (the ability to draw together aspects of thoughts, feelings and actions), both in relation to hypothetical cases. Self‐report questionnaires assessed psychological mindedness, attachment styles, symptoms of burnout and professional qualifications. Results: The preliminary analyses indicated that case formulation skill was associated with higher psychological mindedness (both self‐reported and independently‐rated) and lower levels of avoidant attachment styles. Simultaneous entry multiple regression demonstrated that the only independent predictor of case formulation skill was independently rated psychological mindedness. Conclusions: These findings highlight the factors that contribute to staff's ability to case formulate and the possibility for services to develop psychological mindedness and case formulation skills through formal training, alongside fostering a psychological minded working environment. Practitioner points: Case formulation skill is positively associated with the personal ability (or inclination) to draw together aspects of experience in a psychological manner (i.e., psychological mindedness) It might also be important to consider avoidant attachment tendencies in relation to formulation skills The sample was relatively small and drawn from a limited number of services, which might reduce the generalizability of the findings Psychological mindedness might not be captured adequately by self‐report tools and services may wish to employ more novel ways of assessing this important skill in staff groups (such as the speech sample used in the current study)